Determinant of Pertamax Fuel Demand in Purwokerto - Tami Agustini Fauzan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2018)
This research is aiming to analyze the effect of several factors such as Pertamax price, Pertalite price, income, year of vehicle and vehicle type on Pertamax fuel demand in Purwokerto and analyze which one is the most influencial factors on the Pertamax fuel demand using elasticity test. The data used in this research are primary data taken from 100 respondents all around Purwokerto then analyzed using multiple regression analysis. The result of multiple regression analysis indicated that income and vehicle type have significant effect on Pertamax fuel demand in Purwokerto while the other factors such as Pertamax price, Pertalite price and year of vehicle have no influence on Pertamax demand in Purwokerto. This research also indicated that vehicle type was the most influencial factors on Pertamax demand. From all the result that has been found, the result of regression shows that people in Purwokerto have a tendency to keep putting the quality at any price level set by the government. In this case government have to further intensify massively on advertising on good impact of Pertamax either for machine or environment and expected to improve better performance and quality either in terms of services on each gas station or oil distribution.Keywords: Demand, Pertamax Fuel, Gasoline Demand.